CIMI simulations with newly developed multiparameter chorus and plasmaspheric hiss wave models. Issue 9 (14th September 2017) - Aryan, Homayon; Sibeck, David G.; Kang, Suk‐Bin; Balikhin, Michael A.; Fok, Mei‐Ching; Agapitov, Oleksiy; Komar, Colin M.; Kanekal, Shrikanth G.; Nagai, Tsugunobu
Abstract: Numerical simulation studies of the Earth's radiation belts are important to understand the acceleration and loss of energetic electrons. The Comprehensive Inner Magnetosphere‐Ionosphere (CIMI) model considers the effects of the ring current and plasmasphere on the radiation belts to obtain plausible results. The CIMI model incorporates pitch angle, energy, and cross diffusion of electrons, due to chorus and plasmaspheric hiss waves. These parameters are calculated using statistical wave distribution models of chorus and plasmaspheric hiss amplitudes. However, currently, these wave distribution models are based only on a single‐parameter, geomagnetic index ( A E ) and could potentially underestimate the wave amplitudes. Here we incorporate recently developed multiparameter chorus and plasmaspheric hiss wave models based on geomagnetic index and solar wind parameters. We then perform CIMI simulations for two geomagnetic storms and compare the flux enhancement of MeV electrons with data from the Van Allen Probes and Akebono satellites. We show that the relativistic electron fluxes calculated with multiparameter wave models resemble the observations more accurately than the relativistic electron fluxes calculated with single‐parameter wave models. This indicates that wave models based on a combination of geomagnetic index and solar wind parameters are more effective as inputs to radiation belt models. Key Points: Application of newly developed multiparameter chorus and plasmaspheric hiss wave models CIMI numerical simulations of radiation belt electron flux enhancements Role of chorus and plasmaspheric hiss waves in the dynamics of radiation belts